THE REPRODUCTIVE PERFORMANCE OF THREE IMPORTED HOLSTEIN HERDS IN IRAQ - AL-TIMIMI, LH.; Omran, S.N (The Iraqi Journal of Veterinary Medicine, 2022)
The reproductive performance of three imported Holstein herds in Iraq was investigated in a field study. For this purpose a total number of 889 cows and heifers from three dairy stations that had been on a poor fertility management were palpated rectally for pregnancy determination. Of these, only 289 cows (32.5 %) were pregnant and 541 (60.85 %) were not pregnant. Regarding the non pregnant cows, 385 cows (70.38 % of the non pregnant, 43.3 % of the total) had a normal genital tracts (normal uteri and functional corpora lutea), indicating that they were cycling; the rest had palpable pathological findings; 69 (12.6 % of the total non pregnant) had ovarian inactivity, 56(10.2%) had purulent metritis; 14 (2.55 %) had cervical fibrosis; 12 (2.19 %) had cystic ovary and only two cows (0.36 %) had a mucometritis. The present data indicate low reproductive performance of these herds. Causes of high conception failure in these herds are discussed.